Asymmetric synthesis of aryloxypropanolamines via OsO4-catalyzed asymmetric dihydroxylation - Sayyed, I. A.; Thakur, V. V.; Nikalje, M. D.; Dewkar, Gajanan; Kotkar, S. P.; Sudalai, A. (Tetrahedron, 2005)
A simple and effective procedure for the enantioselective synthesis of several beta-adrenergic blocking agents incorporating the first asymmetric synthesis of celiprolol, is described. The key steps are (i) sharpless asymmetric dihydroxylation of aryl allyl ethers to introduce chirality into the molecules and (ii) conversion of cyclic sulfates into the corresponding epoxides using a three-step procedure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antihypertensive; asymmetric dihydroxylation; cyclic sulfates; epoxides